2018
DOI: 10.1186/s12871-018-0633-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hemodynamic fluctuations after induction of general anesthesia using propofol in non-cardiac surgery: a retrospective cohort study

Abstract: BackgroundAlthough propofol is a common anesthetic agent for the induction of general anesthesia, hemodynamic fluctuations are occasionally prominent during induction/intubation. The aims of this study were to determine the influential factors on enhanced hemodynamic fluctuation and to establish a prediction formula to quickly determine the dose of propofol to protect against hemodynamic fluctuations.MethodsThis retrospective cohort study patients (n = 2097) were 18 years or older. They underwent general anest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 34 publications
0
26
2
5
Order By: Relevance
“…29,30 On the other hand, intraoperative hypotension may predispose negative outcomes such as stroke, AKI, MI, or patient demise. 28 In the present study, no differences in these outcomes were observed.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…29,30 On the other hand, intraoperative hypotension may predispose negative outcomes such as stroke, AKI, MI, or patient demise. 28 In the present study, no differences in these outcomes were observed.…”
Section: Discussioncontrasting
confidence: 58%
“…Predictably, vasopressor burden was higher in the GA-SGA group, a finding likely representing a well-established inherent limitation of GA because anesthetic agents often result in hemodynamic fluctuations secondary to inhibition of sympathetic outflow (particularly during induction). 28 Even though GA-SGA patients received more vasopressors, existing literature on this topic demonstrates that modest intraoperative use of vasopressors to combat hypotension preserves organ perfusion and tissue oxygenation without affecting mortality. 29,30 On the other hand, intraoperative hypotension may predispose negative outcomes such as stroke, AKI, MI, or patient demise.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic fluctuation during the induction of GA is a common event and an important clinical consideration for anesthesiologists [1,8,18]. Jor and colleagues found that hypotension after induction of GA with propofol and sufentanil was observed at ≥1 of the assessed time points in 36.5% patients undergoing elective noncardiac surgery [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, propofol and etomidate have different advantages and adverse effects. Propofol has been associated with injection pain, significant hemodynamic change (hypotension) during induction, and less postoperative nausea and vomiting (PONV) [8][9][10][11]. Etomidate has been associated with less pain during induction, and more stable hemodynamic, with increased myoclonic movements at induction and PONV incidence [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The perturbations in the hemodynamics are more commonly seen during GA . According to the best of our knowledge, there is no study directly comparing the hemodynamic effects of GA and MAC during implantation of S‐ICD.…”
Section: Discussionmentioning
confidence: 99%